Analisis Pernikahan Adat Suku Sasak dan Dampak Ekonominya dalam Perspektif Hukum Islam dan Hukum Positif: Studi Kasus Desa Ketangga Kateng, Kecamatan Praya Barat, Kabupaten Lombok Tengah, NTB - Baiq Dana Mardiana; Ahmad Muti; Mabrurui Andatu (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This research aims to find out how marriage in Sasak customs and its economic impact in the perspective of Islamic and positive law. Perspective of Islamic and positive law. In this case, each tribe has differences in the implementation of the traditional marriage procession, due to the influence of the culture that exists in certain communities, such as the traditional marriage of Lombok. Culture that exists in certain communities, such as traditional marriages in Lombok, this is commonly known as merarik. The type of research used qualitative research with a case study research approach. As for data sources used from primary and secondary data. And for data collection techniques used interviews, observation and documentation. The results showed that: 1) the Sasak tribe's marriage research begins with with escape, selabar, bait wali, akad, perebak pucuk, begawe, metok doe, nyongkolan or rapah, and ends with bales ones naen. Where is the marriage marriage is valid according to Islamic law and state law, but in the process of abduction and process and nyongkolan is not in accordance with the procedures of marriage in Islam. Islam. 2) This traditional Sasak marriage has a significant economic impact. In terms of its economy. This traditional Sasak marriage has a positive impact and a negative impact on the economy. Negative impact on its economy. Where the positive impact can be felt by other communities in order to increase the UMKM of the surrounding community. And the impact The negative impact can be felt by the groom.